Corruption, anti-corruption and governance - Hough, Dan (Political corruption and governance series, 2013)
"Corruption and anti-corruption are now mainstream public policy challenges. Politicians and the public alike now discuss corruption with the type of rhetoric that they never did before. Perhaps surprisingly, however there remains little detailed, cross-national analysis of which anti-corruption strategies work and which don't. This book aims to make a contribution towards redressing this imbalance. Through case studies in six countries (Bangladesh, Kenya, Germany, Poland, South Korea and the UK) this book illustrates that those looking to fight corruption must understand that quality of governance and successful anti-corruption strategies are indelibly linked. Only when this relationship is understood, will progress in tackling corruption be made. The book is empirically rich and theoretically driven, and should be core reading for anyone interested in understanding why corruption flourishes and what works in trying to fight it."--Publisher's website